Erratum to the article “Production of the recombinant hemagglutinin protein of the swine influenza virus A/H1N1 and analysis of its physicochemical and antigenic properties” - E. D. Avdonina; K. A. Pervoykina; L. V. Verkhovskaya; D. N. Shcherbinin; N. Yu. Viskova; I. S. Kruzhkova; M. A. Ilina; L. V. Kudriavtseva; L. V. Kolobukhina; M. M. Shmarov; N. A. Antipyat; A. L. Gintsburg; et al. (Тонкие химические технологии)
.